PENCITRAAN ARAB SAUDI PASCA MUSIM SEMI ARAB - Abyan Ardan Wijaya; Lukman Fahmi Djarwono (Jisiera: The Journal of Islamic Studies and International Relations, 2017)
Kingdom of Saudi Arabia in post Arab Spring (2010-2016) had many strong and unpredictable policies. After Saudi Arabia able to accommodate condition at the Day of Rage, Saudi’s was invading Yemen after evacuating president Hadi to Riyadh. ISIS that became a threat in the north also became one of interest in the Saudi Arabia’s decision making. This kingdom together with Sunni countries cooperating to fight terrorism, giving birth to one of its agenda northern thunder. All of that policies are important policies that need to be made to keep identity, stability, and Saudi legality. This research design is based on identity construction with Alexander Wendt Constructivism, reference to Saudi citizen and values from Saudi citizen identity. The result showed that Saudi Arabia has a state identity construction based on the Quran and Sunnah (tradition) of the Prophet ﷺ, that emphasis on the purity of Islam. This value become the concept brought to the Saudi society. The influence of the ulema is very great, because the Saudis had a strong relations between the ruler and the ulema. The Value and influence of ulema brought decision making was taken from domestic level until international level. These concepts include amar ma’ruf nahi mungkar and manhaj salaf. Both of these concepts are used to address contemporary issues such as political turmoil and terror in the Middle East.